Facing financialization: The divergent mutations of agricultural cooperatives in postapartheid South Africa - (:unkn) unknown (My University, 2018)
This paper analyses the transformation of the South African (former) grain cooperatives since 1994. These entities played a key role in the institutional architecture of the apartheid regime, ensuring the domination of white commercial farmers over the sector. Within the framework of the deregulation of the economy and the agricultural sector, such entities faced transformations of modern capitalism, especially the growing power of financial actors and markets. Although white commercial farmers still largely retain these inherited structures, these companies are presently being targeted more and more by private takeovers and/or private equity deals. Based on two specific empirical examples of private equity deals affecting South African grain cooperatives, this paper describes this financialization process in practice, in particular by analysing the interaction between financial and agricultural actors and the alliances on the ground that determine its “success.” In doing so, it details the different trajectories of these (former) cooperatives, highlighting the resilience, mutation, and extinction of commercial agriculture in South Africa.
Keywords: African Research